2009
DOI: 10.1208/s12249-009-9214-5
|View full text |Cite
|
Sign up to set email alerts
|

Agglomerates Containing Pantoprazole Microparticles: Modulating the Drug Release

Abstract: Abstract. Pantoprazole-loaded microparticles were prepared using a blend of Eudragit® S100 and Methocel® F4M. The accelerated stability was carried out during 6 months at 40°C and 75% relative humidity. In order to improve technological characteristics of the pantoprazole-loaded microparticles, soft agglomerates were prepared viewing an oral delayed release and gastro-resistant solid dosage form. The agglomeration was performed by mixing the pantoprazole microparticles with spray-dried mannitol/ lecithin powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Their advantages include the ability to improve the stability and bioavailability of the drug substance, modification and control of its release site and rate. The most common methods of microparticle production are the solvent evaporation or emulsification method [ 51 , 52 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 ] and spray-drying [ 199 , 200 , 215 , 216 , 217 , 218 , 219 , 220 ]. The advantage of the latter over the other methods is the ease of process scale-up [ 215 ].…”
Section: Development Of New Formulations With Ppismentioning
confidence: 99%
See 1 more Smart Citation
“…Their advantages include the ability to improve the stability and bioavailability of the drug substance, modification and control of its release site and rate. The most common methods of microparticle production are the solvent evaporation or emulsification method [ 51 , 52 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 ] and spray-drying [ 199 , 200 , 215 , 216 , 217 , 218 , 219 , 220 ]. The advantage of the latter over the other methods is the ease of process scale-up [ 215 ].…”
Section: Development Of New Formulations With Ppismentioning
confidence: 99%
“…Among the most commonly used polymers for the manufacturing of microparticles containing proton pump inhibitors are methacrylate derivatives such as Eudragit S and L [ 200 , 202 , 209 , 211 , 215 , 216 , 217 , 219 , 222 ], as well as Eudragit RS/RL [ 199 , 205 , 206 , 214 , 220 ]. Although Eudragit S and L are used to make delayed-release forms of the drug, they can also be used as polymers to formulate sustained-release microparticles [ 200 , 202 , 209 , 211 , 215 , 216 , 217 , 219 , 222 ]. In addition, cellulose derivatives such as ethyl cellulose, HPMC or hydroxypropylmethyl cellulose phthalate are also utilized [ 198 , 203 , 204 , 207 , 208 , 213 , 223 ].…”
Section: Development Of New Formulations With Ppismentioning
confidence: 99%
“…1, F15_70) compared to those without the phospholipid. They were coated by lecithin [45,46] and partially aggregated because lecithin acted as an agglomerating agent. Laser light scattering analysis confirmed that these particles were 4-fold as bigger as without lecithin (Table 2).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…To address this problem, a controlled nanoparticle agglomeration process has been developed where particles exhibiting an aerodynamic diameter from 1 to 5 µm are created to bypass the mouth and throat, resulting in augmented deposition in the lung periphery (Bailey et al, 2008; El-Gendy et al, 2009; Plumley et al, 2009; Schoubben et al, 2010; Tsapis et al, 2002). These porous agglomerates consist of closely-packed nanoparticles that may be easily disseminated throughout the lung (El-Gendy and Berkland, 2009; Raffin et al, 2009; Shi et al, 2007; Tsapis et al, 2002). …”
Section: Introductionmentioning
confidence: 99%